2020
DOI: 10.1021/acs.iecr.0c02412
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Transition from Indirect to Direct Adsorption of Polycyclic Aromatic Hydrocarbons on Quartz: A Combined Theoretical and Experimental Study

Abstract: Adsorption of polycyclic aromatic hydrocarbons (PAHs) on mineral surfaces plays an important role in many engineering fields, such as oil recovery and oil sand production. In this work, the adsorption behaviors of a PAH compound, violanthrone-79 (VO-79), on quartz surface were investigated at different temperatures by molecular dynamics (MD) simulation and atomic force microscopy (AFM). Our simulations demonstrated that with increasing temperature, the rate of adsorption increased, whereas the total amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Our simulations show that adding HEX has no distinct effect on the structure of adsorption of the poly aromatic hydrocarbon on the mineral surface. 35 Although the center of mass of the asphaltenes seems further from the kaolinite surface than toluene, we expect that the presence of oxygen atoms could lead to bonds with the hydroxyl groups on the surface. To confirm this, we calculated the atomic density distribution of 2 oxygen atoms present in the asphaltene structure.…”
Section: Resultsmentioning
confidence: 97%
“…Our simulations show that adding HEX has no distinct effect on the structure of adsorption of the poly aromatic hydrocarbon on the mineral surface. 35 Although the center of mass of the asphaltenes seems further from the kaolinite surface than toluene, we expect that the presence of oxygen atoms could lead to bonds with the hydroxyl groups on the surface. To confirm this, we calculated the atomic density distribution of 2 oxygen atoms present in the asphaltene structure.…”
Section: Resultsmentioning
confidence: 97%
“…Sparks et al proposed that the interface-active components were highly associated with the adsorbed toluene-insoluble organics, which together with the solids played a vital role in stabilizing the emulsions. An opinion is widely held that the properties of the interface-active components, such as particle size distribution and wettability, have a significant influence on the demulsification efficiency . Dongbao et al postulated that colloidal clays could adversely influence the bitumen recovery in the rag layer during the demulsification.…”
Section: Resultsmentioning
confidence: 99%
“…An opinion is widely held that the properties of the interface-active components, such as particle size distribution and wettability, have a significant influence on the demulsification efficiency. 58 Dongbao et al 59 postulated that colloidal clays could adversely influence the bitumen recovery in the rag layer during the demulsification. Hence, the fine solids remaining in the diluted bitumen (top layer in Figure 1) after centrifugation were separated and their characteristics were investigated.…”
Section: Characterizations Of Coarse Solidsmentioning
confidence: 99%
“…329−331 The adsorption behavior of asphaltenes on silica surfaces is favored at higher temperatures. 332 Alumina surfaces, on the other hand, showed a lower affinity for asphaltene adsorption compared to silica surfaces, and the adsorption capacity increases with the acidity of alumina. 333,334 Further, alumina nanoparticles showed enhanced asphaltene adsorption capacity due to spontaneous adsorption and exothermic thermodynamics.…”
Section: Aggregation Of Polyaromatic Macromolecules (Eg Asphaltenes) ...mentioning
confidence: 94%
“…Asphaltene adsorption on silica and alumina surfaces and nanoparticles showed that the adsorption capacity is directly affected by the surface chemistry and morphology of the sorbent and the associated thermal and mechanical conditions. Hydrophilic silica surfaces favor asphaltene adsorption over hydrophobic surfaces. The adsorption behavior of asphaltenes on silica surfaces is favored at higher temperatures . Alumina surfaces, on the other hand, showed a lower affinity for asphaltene adsorption compared to silica surfaces, and the adsorption capacity increases with the acidity of alumina. , Further, alumina nanoparticles showed enhanced asphaltene adsorption capacity due to spontaneous adsorption and exothermic thermodynamics …”
Section: Aggregation Of Polyaromatic Macromolecules (Eg Asphaltenes) ...mentioning
confidence: 99%